Paragdima Integratif Multidisipliner dalam Mempersiapkan pada Program Studi Ekonomi Syariah Berdayasaing - Ihsandi, Aslan Deri; Almizan; Daredmi, Salsabila (SAFE-Network, 2023)
The adoption of the Independent Learning Campus (MBKM) model in the development of the Sharia Economics curriculum is urgent to improve the quality of education to prepare students to face the complexities of the world of work that meets the needs of industry. This study explores the design of the multi-disciplinary integrated paradigm MBKM curriculum in the Sharia Economics study program at UIN Imam Bonjol Padang. This study belongs to the type of research and development with a 4-D (four D) development model. The population consists of students, lecturers, alumni and graduate users, with a sample size of 124. The research results found that the MBKM model with a multidisciplinary integrative paradigm received a high level of agreement of 87%. This indicates that the MBKM approach is considered effective in improving cross-disciplinary skills. In this regard, the development of the Sharia Economics curriculum at UIN Imam Bonjol Padang using an integrative, multidisciplinary MBKM model promises progressive steps, providing freedom to students, and increasing the relevance of graduates to industry needs, creating professionals who are ready to face the dynamics of the world of work.